BUSINESS CULTURE AND SOCIAL MEDIA ENTERPRISE-FACEBOOK SAMPLE - Mesut ATASEVER (Fırat University, 2019)
The incredible and unpredictable rapid and radical changes seen over the past 20 years, cultivating both producers and consumers, as well as business management, have been culturally influenced by the fact that the culture and understanding of business is changing day by day. The most influential elements of business culture are information technology, the internet, especially social media. Perhaps the more effective interaction with people in physical life can come to the fore with social media. The aim of this study is to evaluate how business culture is influenced by social media, especially facebook. This purpose was studied by source scanning, observation and interpretation. With the use of information technologies and the desire to carry social media to businesses, many businesses have started to occupy themselves in different social circles, some businesses have succeeded in this and others have not succeeded. This success and failure may be related to the ability to adapt to change, to recognize trends, and to adaptability. As in all areas where there are crowds, business is developing spontaneously in the field of social media and behaviors are shaped within a specific culture belonging to this field. While it is widespread that social media is only an area of socialization, it is observed that social media is a re-evaluating area that influences both the commercial and general business areas as well as the customer trends. It is expected that this study contributes to this field which is underworked.